Dork diaries dear dork - Russell, Rachel Renee (Simon and Schuster London, 2012)
When Nikki discovers that her arch-nemesis, Mackenzie, has started writing a gossip column for the school newspaper she's worried that Mackenzie might reveal a secret about Nikki's crush, Brandon, that she knows he won't want the whole school to find out about. To keep an eye on what Mackenzie's up to, Nikki joins the newspaper too